Navigating Gender Dynamics in Sport and Physical Activity Employment - González-Rivera, María-Dolores; Guinto, Maria Luisa; Rodríguez-Hernández, María Luisa (International Sports Studies, 2024)
Gender disparity in employment remains a pervasive global issue, and the sport and physical activity (SPA) sector is no exception. Despite a notable increase in women’s sport participation in recent years, this growth has not yet fully translated into significant strides toward gender parity in employment, as men continue to hold most SPA-related occupations. This study investigated the persistent gender inequalities in the SPA industry, focusing on the Madrid region in Spain. A survey was conducted with 400 SPA professionals—102 women and 298 men—to examine occupational representation, employment pathways, employment determinants, contractual arrangements, salary differentials, and organisational affiliations. The findings confirm the underrepresentation of women across all domains of SPA employment, especially in sport coaching for competition. The results showed that recruitment and hiring of women rely primarily on curriculum vitae reviews or public examinations, unlike their male counterparts who lean on their social networks or personal referrals to secure employment in the SPA sector. Findings also revealed that men hold a substantial proportion of formal and informal contracts, including non-contracted jobs, affirming their dominance in both ends of the SPA contractual employment spectrum. Moreover, the study indicated that women often face unfavourable work conditions, including extended working hours and salary differentials. Informed by institutional theory and intersectionality, the discussion highlights the entrenched structures, norms, and practices that reinforce the marginalisation of women based on overlapping identities, sustaining employment practices and outcomes over time. Initiatives are proposed to strengthen equitability and transparency in hiring practices, increase job security, and improve work conditions, enabling organisations and institutions in Madrid to mobilise resources and programmes that foster gender parity in the SPA sector. By advocating gender-informed initiatives that challenge embedded norms and biases, recommendations may be adapted to diverse contexts and cultures where similar gender disparities exist in SPA industries worldwide.